The absorption spectrum of water vapor in the 2.2 μm transparency window: High sensitivity measurements and spectroscopic database. (March 2017) - Campargue, A.; Mikhailenko, S.N.; Vasilchenko, S.; Reynaud, C.; Béguier, S.; Čermák, P.; Mondelain, D.; Kassi, S.; Romanini, D.
Abstract: The weak absorption spectrum of water vapor in the important 2.2 μm transparency window is investigated with very high sensitivity. Overall, about 400 absorption lines were measured by Cavity Ring Down Spectroscopy (CRDS) and Optical-Feedback-Cavity Enhanced Laser Spectroscopy (OF-CEAS) in five spectral intervals: 4248.2–4257.3, 4298.4–4302.6, 4336.8.5-4367.5, 4422.4-4441.2 and 4514.6-4533.7 cm −1 . The achieved sensitivity of the recordings (noise equivalent absorption, α min, on the order of 2×10 −10  cm − 1 ) allowed detecting transitions with intensity values down to 1×10 − 28 cm/molecule, more than one order of magnitude better than previous studies by Fourier Transform spectroscopy. The rovibrational assignment was performed on the basis of variational calculations and of previously determined empirical energy values. Most of the newly assigned lines correspond to transitions of the ν1, ν3 and 3ν2 bands of H2 17 O in natural isotopic abundance. Fourteen energy levels of H2 17 O, H2 18 O and HD 18 O are newly determined. An accurate and complete spectroscopic database is constructed for natural water in the 4190–4550 cm − 1 region (2.39–2.20 µm). The list includes about 4500 transitions with intensity greater than 1×10 − 29  cm/molecule, for the six most abundant isotopologues in natural isotopic abundance. Line positions were obtained by difference of empirical energy values determined from literature data and complemented with the present CRDS results. The list is made mostly complete by including weak transitions not yet detected, with positions calculated from empirical levels and variational intensities. The variational intensities computed by a collaboration between the University College London and the Institute of Applied Physics in Nizhny Novgorod are found to improve significantly previous results by Schwenke and Partridge. Examples of comparison of the constructed line list to CRDS spectra and to simulations based on the HITRAN2012 list illustrate the advantages of the new list. The absence of many HDO lines is identified as most important deficiency of the HITRAN2012 list in the region. Graphical abstract: Highlights: High sensitivity CRDS and OF-CEAS of water vapor in the 2.2 µm transparency window. About 400 lines measured and rovibrationallly assigned in five spectral intervals. Comparison with previous FTS studies, HITRAN2012 and variational calculations. A spectroscopic database is constructed for natural water between 4190 and 4550 cm − 1 . It includes empirical positions, variational intensities and line profile parameters.